2022
DOI: 10.3390/cancers14143463
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-Mediated Fibrosis in the Out-of-Target Heart following Partial-Body Irradiation

Abstract: Recent reports have shown a link between radiation exposure and non-cancer diseases such as radiation-induced heart disease (RIHD). Radiation exposures are often inhomogeneous, and out-of-target effects have been studied in terms of cancer risk, but very few studies have been carried out for non-cancer diseases. Here, the role of miRNAs in the pathogenesis of RIHD was investigated. C57Bl/6J female mice were whole- (WBI) or partial-body-irradiated (PBI) with 2 Gy of X-rays or sham-irradiated (SI). In PBI exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
0
7
0
2
Order By: Relevance
“…Honaryar et al [ 13 ] conducted a prospective study of 101 breast cancer patients who received radiotherapy but not chemotherapy, and found that at two years after radiotherapy, early progression of calcification in the left anterior descending coronary artery is associated with radiation exposure of the left ventricle. Tanno et al [ 14 ] performed microRNome analysis in the heart of wild-type mice whose whole bodies or partial (lower one-third) bodies were irradiated, and revealed the differential expression of microRNAs belonging to the myomiR family in the heart of whole body- or partial body-irradiated mice. Tanno et al [ 14 ] also conducted in vitro experiments whereby irradiated skeletal muscle cells and non-irradiated ventricular cells were co-cultured, and proposed miR-1/133a as a potential mediator of the abscopal (out-of-field) response in non-directly irradiated tissues.…”
Section: Overview Of Published Articlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Honaryar et al [ 13 ] conducted a prospective study of 101 breast cancer patients who received radiotherapy but not chemotherapy, and found that at two years after radiotherapy, early progression of calcification in the left anterior descending coronary artery is associated with radiation exposure of the left ventricle. Tanno et al [ 14 ] performed microRNome analysis in the heart of wild-type mice whose whole bodies or partial (lower one-third) bodies were irradiated, and revealed the differential expression of microRNAs belonging to the myomiR family in the heart of whole body- or partial body-irradiated mice. Tanno et al [ 14 ] also conducted in vitro experiments whereby irradiated skeletal muscle cells and non-irradiated ventricular cells were co-cultured, and proposed miR-1/133a as a potential mediator of the abscopal (out-of-field) response in non-directly irradiated tissues.…”
Section: Overview Of Published Articlesmentioning
confidence: 99%
“…Tanno et al [ 14 ] performed microRNome analysis in the heart of wild-type mice whose whole bodies or partial (lower one-third) bodies were irradiated, and revealed the differential expression of microRNAs belonging to the myomiR family in the heart of whole body- or partial body-irradiated mice. Tanno et al [ 14 ] also conducted in vitro experiments whereby irradiated skeletal muscle cells and non-irradiated ventricular cells were co-cultured, and proposed miR-1/133a as a potential mediator of the abscopal (out-of-field) response in non-directly irradiated tissues. Mpweme Bangando et al [ 15 ] irradiated the aortic valves of mice defective in transient receptor potential melastatin 4 (TRPM4, monovalent non-selective cation channel) or their wild-type counterparts, and found that TRPM4 is involved in aortic valve remodeling after irradiation.…”
Section: Overview Of Published Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…About two-thirds of the heart’s cells are fibroblasts, which are located in the connective tissue. They play a role in a variety of cardiac functions, such as controlling the ECM’s equilibrium, rebuilding the ECM, and producing growth factors and cytokines [ 124 ]. The typical role of fibrocyte cells is to secrete collagen and support the heart’s structural integrity.…”
Section: Effect Of Fibrosis On Different Organsmentioning
confidence: 99%
“…For kidneys, the AHS study has shown an increased radiation risk of chronic kidney disease (CKD) and suggested a role of CKD in CVD development ( 133 ). Studies in rats have shown that targeted kidney irradiation induces remodeling of the nontargeted heart mediated in part by the immune response ( 134 , 135 ), perhaps also by other mechanisms such as microRNAs ( 136 ), suggesting a role of kidney injury in radiogenic heart disease. Considering that CVD risk factors include diabetes and that an increased radiation risk of diabetes have been observed after high dose, fractionated radiotherapy ( 137139 ), the pancreas may be a candidate target, although radiation risk of diabetes at lower dose is uncertain ( 115 ).…”
Section: Recent Developments For Effects On the Circulatory Systemmentioning
confidence: 99%